Radio-guided localization of clinically occult breast lesions: current modalities and future directions. (January 2014) - Aydogan, Fatih; Velidedeoglu, Mehmet; Kilic, Fahrettin; Yilmaz, Halit
Abstract : The extensive availability of breast cancer screening programs and improvement in diagnostic imaging have led to more frequent detection of suspicious and clinically occult breast lesions. Early detection of tumor is important for breast-conserving treatment. Incomplete excision is a major risk factor for local recurrence. Following precise localization and removing the entire lesion while achieving adequate clear margins is the key factor for successful management of non-palpable breast lesions. For this purpose, several techniques such as wire-guided localization, intra-operative ultrasound guided resection, radio-guided occult lesion localization and radioactive seed localization have been described and applied. In this article, we overview the two commonly used localization techniques, radio-guided occult lesion localization and wire-guided localization, particularly describing their advantages and drawbacks.